Selective CO2 capture and versatile dye adsorption using a microporous polymer with triptycene and 1, 2, 3-triazole motifs. (February 2018) - Bera, Ranajit; Ansari, Mosim; Mondal, Snehasish; Das, Neeladri
Graphical abstract: Highlights: Synthesis of triptycene based and 1, 2, 3-triazole linked microporous polymer (TTMP ). TTMP exhibits high surface area. High H2 uptake of 14.2 mg g −1 at 77 K and 1 bar. High CO2 uptake (16.3 wt% at 273 K & 1 bar) and CO2 /N2 selectivity (85 at 273 K). High dye removal capacity: 1000 mg/g (Congo Red) and 405 mg/g (Rhodamine B). Abstract: Polymerization of 2, 6, 14-triethynyltriptycene and 1, 3, 5-tris(azidomethyl)-2, 4, 6-trimethylbenzene to yield a new microporous organic material (TTMP ) is described.TTMP is thermally stable polymer with a high surface area, rendering it suitable to act as an adsorbent for gases such as CO2 and H2 as well as for organic small molecule adsorbates such as toxic organic dyes present in effluents discharged from textile industry.TTMP has the potential as a material with applications in the domain of gas storage/separation and water pollution control.